Shy (modest, shame) feelings and experiences in committing immoral acts among Malay and Chinese adolescents - Muhammad, Zarina; Abdullah, Akmaliza; Ab Razak, Ratna Roshida; Buliah, Amirah (Human Resource Management Academic Research Society, 2022)
Every race and religion, especially the Malays and Chinese, have been found to make shyness a part of their characteristics as a deterrent from doing wrong and immoral behaviour in their society. However, the statistics of moral problems, including criminal acts among adolescents, which are increasing and terrifying every year, indirectly show that the nature of shame in committing immoral acts in society has been eroded. Thus, this study aims to explore the shame experienced by Malay and Chinese youth in committing immoral acts. This study uses the survey method. According to the mapping done on Malaysian adolescents, this study focuses on Malay and Chinese adolescents from the four districts with the highest percentage of adolescent involvement in deviant behaviour in Selangor. The districts are Petaling, Ulu Langat, Kelang, and Gombak. The study results showed that the adolescents in the above district still feel and experience shame and shyness and the degree of shame in doing a bad, wrong, and immoral act is still high.